PROJECT-BASED LEARNING INTEGRATED TO STEM (STEM-PJBL) TO ENHANCE ARABIC LEARNING HOTS-BASED - Harun, Uhame Binti (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2020)
HOTS are the skills needed at this time. STEM-PjBL model is one learning model that can be applied to improve students' higher-order thinking skills. STEM-PjBL is learning that integrates four fields, namely science, technology, engineering, and mathematics, which are project-based learning. Therefore, this learning model encourages students to be active, creative, and innovative in learning, which is in line with the educational goals in Learning Arabic as a foreign language. The research method in this article descriptively is library research. Data obtained from the results of literature studies in the form of books and articles relating to STEM-PjBL using the technique of documentation or searching of library sources for data collection. Data analysis techniques using data triangulation. This study shows that the STEM-PjBL learning model is a learning model that can improve students' higher-order thinking skills (HOTS). Also, learning Arabic can use the STEM-PjBL learning model.